(untitled) (Revista Sistemas de Producción Agroecológicos, 2021)
The use of different technologies and resources related to the feeding of pigs should be focused on a continuous improvement of the conditions of the animals, which satisfies their nutritional requirements (in quantity and quality) and allows them a good performance, which is evidenced in the productive and reproductive parameters, as well as in the health and well-being of the herd. Nutrition is one of the pillars that sustains the production of pigs, either to guarantee the final product of good quality or because it is the component with the greatest weight in the final cost of production. The main components that supply the energy requirements of pigs are carbohydrates and lipids. Corn is the main source of energy used in pig feeding, it contains digestible and metabolizable energy levels of 3.5 and 3.3 Mcal / kg, respectively. While fats and oils provide 9.0 to 9.5 Mcal / kg of digestible energy, being considered a very good source of energy, but these lipid components are only added at levels of 3 to 5% in the diet. A difference that exists between the components of the diet is due to the caloric increase (IC), represented by the increase in heat production after the consumption of food by the animal. On the other hand, a very common problem in the use of fats and oils in the formulation of diets is rancidity. Factors such as temperature, enzymes, light and metal ions can influence the formation of free radicals that in contact with molecular oxygen leads to the formation of a peroxide. The reaction with another oxidizable molecule induces the formation of hydroperoxide and another free radical. Hydroperoxides give rise to two free radicals capable of attacking other molecules and forming more free radicals. When the formed molecules break, they generate lower molecular weight products such as aldehydes, ketones, alcohols and esters, which are volatile and responsible for rancification. When fat is subject to oxidation and becomes rancid, it reduces its palatability and can be the cause of nutritional and digestive problems.